Development and validation of ultra-performance liquid chromatography-tandem mass spectrometric methods for simultaneous and rapid determination of contezolid and its major metabolite M2 in plasma and urine samples and its application to a study in subjects with moderate liver impairment - Wang, Yu; Wu, Hailan; Wu, Junzhen; Fan, Yaxin; Liu, Xiaofen; Li, Yi; Hu, Jiali; Zhang, Jing; Guo, Beining (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2022)
•Information on analytical methods in biological samples is limited.•Reliable UPLC-MS/MS methods for simultaneous determination of contezolid and M2.•Successful application of the validated assays to a clinical pharmacokinetic study. Contezolid is a novel oxazolidinone antibiotic with good antibacterial activity against gram-positive bacteria including methicillin-resistant Staphylococcus aureus. For the purpose to further characterize the pharmacokinetics of contezolid and its major metabolite M2, accurate and rapid ultra-performance liquid chromatography-tandem mass spectrometric assays (UPLC-MS/MS) were developed and validated for simultaneous quantification of contezolid and M2 in human plasma and urine. The plasma samples were pretreated by liquid–liquid extraction. The automated solid phase extraction method was used to preprocess urine samples. ACQUITY UPLC® BEH C8 (2.1 mm × 100 mm, 1.7 µm) column was used to separate the analytes with a gradient mobile phase of acetonitrile and water at a flow rate of 0.4 mL/min. The calibration curves showed good linearity over the concentration ranges of 0.0100–5.00 µg/mL for contezolid in plasma and urine, 0.00200–1.00 µg/mL in plasma and 0.0200–10.0 µg/mL in urine for M2, respectively. For both plasma and urine assays, the intra- and inter-batch accuracy and precision were within 15% for all quality control levels, including the lower limit of quantitation. The methods were fully validated and successfully applied to a pharmacokinetic study of contezolid tablets in subjects with moderate hepatic impairment.